The Risk Factor of Subclinical Mastitis Incident in Dairy Cattle in KPSP Ijen Makmur, Banyuwangi - Ningrum, Indah Puspita; Soeharsono, Soeharsono; Wibawati, Prima Ayu; Dhamayanti, Yeni; Yunita, Maya Nurwartanti (Universitas Airlangga, 2022)
Mastitis is an inflammatory disease in the internal tissue of the mammary gland. Subclinical mastitis does not show any changes in the shape of the mammary gland and to detect it can be examined the number of somatic cells in milk. Subclinical mastitis uses the California Mastitis Test (CMT) method as preliminary research to obtain preliminary data on the incidence of subclinical mastitis in KPSP Ijen Makmur, Licin District, Banyuwangi Regency. This research is descriptive research. The detection for this research was carried out by taking milk samples in cows per purposive and reacted CMT reagents issued circularly for 10-15 seconds. Observation of results is determined based on changes inconsistency with the existence of gel and the results of interview farmers as supporting data. The results showed that the influencing factors incidence of subclinical mastitis in KPSP Ijen Makmur, Licin District, Banyuwangi Regency were milk production, age and amount of lactation. In contrast, the biggest factor for reducing the risk of subclinical mastitis is udder health followed by body conditions measured by Body Condition Score.